Caffeine ingestion improves repeated freestyle sprints in elite male swimmers - Goods, P. S. R.; Landers, G.; Fulton, S. (Journal of Sports Science & Medicine, 2017)
The purpose of this investigation was to determine the efficacy of a moderate dose of caffeine to improve repeat-sprint performance in elite freestyle sprinters. Nine highly trained male swimmers performed 6 x 75 m freestyle sprints on two occasions 1-h after consuming either 3 mg·kg-1 caffeine (CAF), or placebo, in a cross-over manner. Capillary blood samples for the analysis of blood lactate concentration and pH were collected after the 1st, 3rd, and 5th sprint, while heart rate and perceived exertion (RPE) were collected after every sprint. There was a moderate effect for improved mean sprint time in the CAF condition (0.52 s; 1.3%; d = 0.50). When assessed individually, there was a large effect for improved performance in sprints 3 (1.00 s; 2.5%; d = 1.02) and 4 (0.84 s; 2.1%; d = 0.84) in CAF compared to placebo, with worthwhile performance improvement found for each of the first 5 sprints. There was a significant treatment effect for higher blood lactate concentration for CAF (p = 0.029), and a significant treatment*time effect for reduced pH in the CAF condition (p = 0.004). Mean heart rate (167 ± 9 bpm vs 169 ± 7 bpm) and RPE (17 ± 1 vs 17 ± 1) were not different between placebo and CAF trials, respectively. This investigation is the first to demonstrate enhanced repeat-sprint ability in swimmers following acute caffeine ingestion. It appears likely that the combination of a moderate dose of caffeine (3-6 mg·kg-1) with trained athletes is most likely to enhance repeat-sprint ability in various athletic populations; however, the exact mechanism(s) for an improved repeat-sprint ability following acute caffeine ingestion remain unknown.